A critical role for estrogen signaling in penis development. Issue 9 (21st June 2019) - Govers, Luke C.; Phillips, Tiffany R.; Mattiske, Deidre M.; Rashoo, Nineveh; Black, Jay R.; Sinclair, Adriane; Baskin, Laurence S.; Risbridger, Gail P.; Pask, Andrew J.
ABSTRACT: Hypospadias, a developmental defect of the penis, is one of the most common congenital malformations in humans. Its incidence has rapidly increased over recent decades, and this has been largely attributed to our increased exposure to endocrine‐disrupting chemicals. Penis development is primarily an androgen‐driven process; however, estrogen and xenoestrogens are known to affect penis development in both humans and mice. Here, we investigated the role of estrogen in the developing penis. Using a novel penis culture system, we showed that exogenous estrogen directly targets the developing penis in utero to cause hypospadias. In addition, we also uncovered an unexpected endogenous role for estrogen in normal postnatal penis development and showed that a loss of estrogen signaling results in a mild hypospadias phenotype, the most common manifestation of this disease in humans. Our findings demonstrated that both androgen and estrogen signaling are intrinsically required for normal urethral closure. These findings confirmed that penis development is not an entirely androgen‐driven process but one in which endogenous estrogen signaling also plays a critical role.—Govers, L. C., Phillips, T. R., Mattiske, D. M., Rashoo, N., Black, J. R., Sinclair, A., Baskin, L. S., Risbridger, G. P., Pask, A. J. A critical role for estrogen signaling in penis development. FASEB J. 33, 10383†10392 (2019). www.fasebj.org